Optimal information structures in bilateral trade. Issue 1 (21st January 2023) - Schottmüller, Christoph
Abstract : With the goal of maximizing expected gains from trade, this paper analyzes the jointly optimal information structure and mechanism in a bilateral trade setting. The difference in gains from trade between the optimal information structure and first best constitutes the minimal loss due to asymmetric information. With binary underlying types it is shown that more than 95% of first best can be achieved while the optimal mechanism without information design may achieve less than 90% of first best. For more general type distributions, the optimal information structure is a monotone partition of the type space and the optimal mechanism is deterministic. Necessary conditions for the optimal information structure are derived and a closed form solution is given for the binary type case.